DIAGNOSIS PENYAKIT MOSAIK (SOYBEAN MOSAIC VIRUS) TERBAWA BENIH KEDELAI - Wuye Ria Andayanie (Universitas Lampung, 2012)
Soybean mosaic disease is wide spread throughout soybean-growing countries. Incidence of this disease in East Java is caused by Soybean mosaic virus (SMV) and cowpea mild mottle virus (CMMV). This aim of study was to find the etiology of disease at 14-28 days after planting (dap) on soybean. Research was done by observing visual symptoms. Visual symptoms confirmed by infectivity test, serology assay,electron microscopy (EM) and molecular detection. Results from experiment indicated that soybean plants (14-28 dap) with symptom could be detected in infectivity test. Mechanical inoculation with symptomatic leaf extracts produced local lessions on Chenopodium amaranticolor. Positive results were obtained for Madiun, Ngawi, and Magetan samples when tested against antiserum of SMV in serological assay, however Ponorogo samples were not detected by serological assay. Electron microscopy was also done for the selected sample to confirm the result of positive results. In EM observations, characteristic filamentous particles with modal length close to 900 nm were observed in samples infected with SMV. We detected an array of amplification products of expected size 1385 bp fragment of cylindrical inclusion gene from Madiun, Ngawi, and Magetan isolates in former fields, but not detected in Ponorogo isolate. This result showed the existence of SMV of soybean seed transmission at 14-28 dap in Madiun, Magetan and Ngawi.